Comparison of TPF and TP Induction Chemotherapy for Locally Advanced Nasopharyngeal Carcinoma Based on TNM Stage and Pretreatment Systemic Immune-Inflammation Index - Xiong, Ying; Shi, Liangliang; Zhu, Lisheng; Peng, Gang (Frontiers in Oncology, 2021)
Purpose: To compare the efficacy and toxicity of two IC regimens, TPF (taxanes, cisplatin and 5-fluorouracil) and TP (taxanes and cisplatin), followed by concurrent chemoradiotherapy (CCRT) in locally advanced nasopharyngeal carcinoma (LA-NPC). Methods: 213 patients diagnosed with LA-NPC (stage III-IVA) were included retrospectively. The prognosis of TPF and TP was compared by Kaplan-Meier and Cox proportional hazard regression. The treatment-related toxicities were evaluated according to CTCAE v4.0 and RTOG criteria. Results: TPF was found to have a higher 5-year DMFS in stage IVA and N2-3 patients, which not applicable to stage III and N0-1. The optimal value of pre-treatment SII was 432.48. A further subgroup analysis revealed that patients in stage IVA combined with pretreatment SII≥432.48 could get higher OS (P=0.038) and DMFS (P=0.028) from TPF. Multivariate analysis showed that SII was a prognostic factor for PFS (HR 2.801, P=0.018) and DMFS (HR 3.735, P=0.032), and IC regimen (HR 2.182, P=0.049) for predicting DMFS. The rate of grade 3-4 leukopenia (P=0.038), neutropenia (P=0.021), radiation oral mucositis (P=0.048) and diarrhea (P=0.036) were more common in TPF group. Conclusion: Our study revealed that TPF regimen showed a higher 5-year DMFS for stage IVA and N2-3 patients, while TP may be enough for stage III and N0-1. In LA-NPC patients with high risk (stage IVA combined with pre-treatment SII ≥ 432.48), TPF had a higher 5-year OS and DMFS, although grade 3-4 toxicities were more common but tolerable.